Hard-templating of chiral TiO2 nanofibres with electron transition-based optical activity. Issue 5 (22nd October 2015) - Wang, Cui; Liu, Shaohua; Duan, Yingying; Huang, Zhehao; Che, Shunai
Abstract: The fabrication of optically active inorganic nanomaterials with chiral superstructures attracts attention because of their potential applications in chemical sensing and non-linear optics. Here, we present a facile way to prepare TiO2 nanofibres, in which the nanocrystals are helically arranged into a chiral superstructure. Notably, the chiral superstructure shows strong optical activity due to the difference of absorbing left- and right-handed circularly polarized light. This special optical activity resulted from electron transition from the valence band to the conduction band of TiO2 through a vicinal effect of helically arranged TiO2 nanocrystals.